Water quality improver for aquaculture and method for preparing the same
Patent Information
- Application Number
- CN202510963644.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-14
AI Technical Summary
[0006]本发明的目的在于解决传统水质改良剂中使用高风险抗菌组分(如纳米银)导致的生态毒性和环境污染问题,同时提升水质改良效果的可持续性和安全性,而提供一种水产养殖用水质改良剂及其制备方法
1、本发明通过将核桃壳衍生物酸洗煅烧,得到预处理生物碳,负载二氧化钛/铁-锰纳米片,得到复合型生物碳,其复合型生物碳结合了生物碳的吸附效果和二氧化钛/铁-锰纳米片的光催化效果,形成多功能复合材料;抗菌型复合水凝胶将益生菌核壳微球嵌入明胶-单宁酸水凝胶中,实现益生菌的缓释保护、物理屏障抗菌;协同实现“吸附-光催化降解-生物抗菌”三位一体,显著提升有机物去除率与水质稳定性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water quality improvement technology, specifically relating to a water quality improver for aquaculture and its preparation method. Background Technology
[0002] With the advancement of aquaculture technology, high-density aquaculture has become an industry trend. This has led to ponds being unable to effectively remove pollutants such as uneaten feed and fish and shrimp feces, resulting in serious exceedances of ammonia nitrogen, nitrite, and sulfides in the aquaculture water. Consequently, pond water quality has deteriorated, and fish and shrimp diseases have become more frequent. To address the water quality deterioration caused by high-density aquaculture, it is necessary to develop a new type of aquaculture water quality improver to achieve efficient and low-cost purification of aquaculture water.
[0003] Water quality improvers are substances or methods used to improve water quality. They can be achieved by adding specific chemical substances or by adopting specific treatment methods. Among them, aquaculture water quality improvers are chemical substances or biological agents used to improve and optimize the aquatic environment of aquaculture. They are usually designed to adjust the physical, chemical and biological characteristics of the water body to create a more suitable environment for the survival and growth of farmed species. They can be divided into two main categories: physical and chemical. Chemical water quality improvers are mainly chemical disinfectants of the strong oxidant type, such as sodium percarbonate, potassium peroxymonosulfate compound salt and calcium peroxide. These improvers can not only improve the water environment, the bottom quality of the water body and enhance the oxygenation of the water body, but also disinfect, sterilize, detoxify and inhibit bacteria.
[0004] Chinese invention patent application CN 117446886A discloses an aquatic water quality improver and its preparation method. The improver achieves stronger adsorption and flocculation effects through a hydroxylamine reaction between active amino and hydroxyl groups, and a synergistic effect with the reaction of nano-silver coated zinc oxide. Copper sulfate and yeast undergo a bridging reaction, which further enhances the adsorption and flocculation effects. The yeast can produce bioactive substances through its own metabolism, thereby achieving sterilization.
[0005] Among them, zinc oxide coated with nano-silver is used as an antibacterial component. However, nano-silver tends to accumulate in organs such as gills and liver of aquatic organisms. Long-term use may lead to chronic poisoning or food chain transmission risks. In particular, it has a non-selective killing effect on phytoplankton and probiotics, which may disrupt the ecological balance of aquatic bodies. Summary of the Invention
[0006] The purpose of this invention is to solve the ecotoxicity and environmental pollution problems caused by the use of high-risk antibacterial components (such as nano-silver) in traditional water quality improvers, while improving the sustainability and safety of water quality improvement effects, and to provide an aquaculture water quality improver and its preparation method.
[0007] This invention obtains pretreated biochar by acid washing and calcining walnut shell derivatives, which is then loaded with titanium dioxide / iron-manganese nanosheets to obtain composite biochar. A composite bacterial community is then coated with sodium alginate-calcium chloride to form core-shell microspheres, and gelatin-tannic acid hydrogel is added for sustained release, resulting in an antibacterial composite hydrogel. The composite biochar, bentonite, deionized water, and hollow glass microspheres are ball-milled to obtain the main material. Cod liver oil is homogenized and emulsified with the antibacterial composite hydrogel to obtain the auxiliary material. This material is then processed using a pelletizing machine to obtain an aquaculture water quality improver.
[0008] The objective of this invention can be achieved through the following technical solutions: An aquaculture water quality improver, comprising the following raw materials by weight: 40-50 parts composite biochar, 8-10 parts bentonite, 50-60 parts deionized water, 8-10 parts hollow glass microspheres, 16-20 parts cod liver oil and 35-40 parts antibacterial composite hydrogel; Composite biochar is prepared by combining walnut shell derivatives with titanium dioxide / iron-manganese nanosheets; Titanium dioxide / iron-manganese nanosheets are prepared by the following steps: Ferric chloride hexahydrate, manganese sulfate, and deionized water were stirred to obtain a mixed metal solution. Anatase nano-titanium dioxide, deionized water, the mixed metal solution, 1 wt% sodium citrate solution, and 1 wt% ascorbic acid solution were stirred under nitrogen atmosphere in the dark and then photocatalytically reduced to obtain titanium dioxide / iron-manganese nanosheets.
[0009] Furthermore, the composite biochar is prepared through the following steps: Walnut shell derivatives were acid-washed and refluxed for 1-2 hours, washed with ultrapure water until neutral, filtered, dried, and calcined at 400-500℃ under nitrogen protection for 2-3 hours to obtain pretreated biochar. Titanium dioxide / iron-manganese nanosheets, pretreated biochar, and deionized water were added to a reaction vessel and stirred at 300-400 rpm for 2-3 hours. The mixture was then transferred to a 500 mL stainless steel reaction vessel lined with polytetrafluoroethylene and reacted at 160-180℃ for 6-8 hours. After cooling to room temperature, the mixture was filtered, vacuum dried at 70-80℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain composite biochar.
[0010] Furthermore, the ratio of titanium dioxide / iron-manganese nanosheets, pretreated biochar, and deionized water is 9-15g:1-3g:240-300mL.
[0011] Furthermore, the titanium dioxide / iron-manganese nanosheets are prepared by the following steps: Ferric chloride hexahydrate, manganese sulfate, and deionized water were added to a reaction vessel and stirred at 60-70℃ for 10-15 min to obtain a mixed metal solution. Anatase nano-titanium dioxide and deionized water were added to the reaction vessel and sonicated for 20-30 min. Then, the mixed metal solution, 1 wt% sodium citrate solution, and 1 wt% ascorbic acid solution were added. Nitrogen gas was introduced for 20-30 min, and the mixture was stirred in the dark at 300-350 rpm for 20-30 min. A 365 nm ultraviolet lamp was placed 5-10 cm below the liquid surface and the lamp was turned on. The mixture was reacted in a water bath at 40-50℃ for 3-4 h. The suspension turned brownish-black. The mixture was filtered and washed repeatedly with 1 wt% sodium citrate solution and nitrogen-saturated ethanol until the water was clear. The mixture was then vacuum dried to constant weight to obtain titanium dioxide / iron-manganese nanosheets.
[0012] Furthermore, the ratio of ferric chloride hexahydrate, manganese sulfate, and deionized water is 4.5-5.5g: 4.5-5.5g: 90-100mL; The ratio of anatase nano-titanium dioxide, deionized water, mixed metal solution, sodium citrate solution, and ascorbic acid solution is 9.0-11.0g: 0.9-1.0L: 45-55mL: 90-100mL: 450-550mL.
[0013] Furthermore, the antibacterial composite hydrogel is prepared by the following steps: Add the composite bacterial solution to the reaction vessel, centrifuge for 10-15 min, collect the bacterial cells, transfer to phosphate buffer and 4 wt% sodium alginate solution and stir for 20-30 min, then add 0.1 wt% calcium chloride solution dropwise and solidify for 20-30 min to obtain core-shell antibacterial microspheres; add gelatin and deionized water to the reaction vessel and stir at 50-60℃ for 20-30 min, add tannic acid, adjust the pH to 8 with sodium hydroxide, stir for 10-15 min, then add the core-shell antibacterial microspheres, stir for 5-10 min, pour into a mold and freeze at -30℃ to -20℃ for 1-2 h, thaw at room temperature to obtain antibacterial composite hydrogel.
[0014] Furthermore, the ratio of the volume of the compound bacterial solution, phosphate buffer, sodium alginate solution, and calcium chloride solution is 20-30 mL: 5-10 mL: 10-15 mL: 0.8-1.0 mL; The ratio of gelatin, deionized water, tannic acid and core-shell antibacterial microspheres is 3.0-3.5g: 30-40mL: 0.5-1.0g: 0.5-1.0g.
[0015] Furthermore, the compound bacterial solution is prepared by the following steps: Add 1.5wt% shrimp shell hydrolysate, 0.3wt% fish meal peptone, 0.04wt% sodium nitrate and 0.1wt% riboflavin solution to a reaction vessel, adjust the pH to 6 with deionized water to obtain a compound bacterial culture medium; inoculate Bacillus licheniformis suspension, Bacillus subtilis suspension, Rhodopseudomonas palustris suspension, Rhodopseudomonas sphaeroides suspension and enzyme-producing lysinus suspension into the compound bacterial culture medium, and culture at 30-40℃ for 100-120h to obtain a compound bacterial solution.
[0016] Furthermore, the mass ratio of shrimp shell hydrolysate, fish meal peptone, sodium nitrate, and riboflavin is 3-5:0.6-0.8:0.08-0.1:0.2-0.4; The ratio of Bacillus licheniformis suspension, Bacillus subtilis suspension, Rhodopseudomonas palustris suspension, Rhodopseudomonas sphaeroides suspension, enzyme-producing lysinus suspension, and compound culture medium is 1.8-2.2 mL: 1.8-2.2 mL: 2.4-3.0 mL: 3.0-3.6 mL: 1.0-1.5 mL: 200-300 g.
[0017] Furthermore, a method for preparing an aquaculture water quality improver includes the following steps: Step 1: Add composite biochar, bentonite, and deionized water to a ball mill and mill for 20-30 minutes. Then add hollow glass microspheres and mill for 10-20 minutes to obtain the main material. Add cod liver oil and antibacterial composite hydrogel to an emulsifier and homogenize and emulsify for 10-15 minutes to obtain the auxiliary material. Step 2: Close the glue outlets on both sides of the fully automatic pellet press, preheat the glue outlets to 30-40℃, connect the glue tube and air tube, and transport the main material into the gelatin box. Open the glue outlet to form a continuous gelatin strip. When the strip passes through the rotating mold, add the auxiliary material. The mold presses the strip to form an elliptical pellet. Dry it at 30-40℃ for 2-3 hours, spray it with a 10wt% citric acid ethanol solution for 10-15 seconds, and vacuum dry it to obtain an aquaculture water quality improver.
[0018] The application method of aquaculture water quality improver includes the following steps: For open ponds, use water quality improver at 200g / mu·m; for recirculating water systems, add 50g / m³. 3 For cage culture, use 100g / bag (net bag: 40×60cm) per 10m² 3 Hang one bag; before use, mix 1g of improver with 10mL of water and stir for 10-20 minutes to activate it. After activation, in open ponds, evenly sprinkle it against the wind and inject it into the circulating water system according to the ratio. The net cages are suspended at a water depth of 1.5-3m. Oxygenation should be carried out simultaneously throughout the addition process to promote the release of active substances through water flow.
[0019] The beneficial effects of this invention are: 1. This invention obtains pretreated biochar by acid washing and calcining walnut shell derivatives, and then loads titanium dioxide / iron-manganese nanosheets to obtain composite biochar. The composite biochar combines the adsorption effect of biochar with the photocatalytic effect of titanium dioxide / iron-manganese nanosheets to form a multifunctional composite material. The antibacterial composite hydrogel embeds probiotic core-shell microspheres into gelatin-tannic acid hydrogel to achieve slow-release protection of probiotics and physical barrier antibacterial effect. It synergistically achieves the three-in-one effect of "adsorption-photocatalytic degradation-biological antibacterial", which significantly improves the organic matter removal rate and water quality stability.
[0020] 2. The titanium dioxide / iron-manganese nanosheets in this invention utilize iron and manganese doping to broaden the titanium dioxide spectrum, improve light energy utilization, and efficiently degrade organic pollutants. The iron and manganese oxides specifically remove heavy metals such as lead and cadmium through complexation adsorption and redox reactions, and reduce highly toxic chromium to a less toxic form. After settling in water, they oxidize the organic matter in the bottom sediment, inhibit the generation of hydrogen sulfide, and work synergistically with probiotics to repair the microecology.
[0021] 3. The composite biochar in this invention forms ultra-porous structures in walnut shells through acid washing and calcination, which strongly captures ammonia nitrogen and heavy metals. The loaded titanium dioxide / iron-manganese nanosheets are excited with active oxygen under visible light, which degrades and adsorbs pollutants in situ, improving the material's renewability efficiency. The surface functional groups and nano gaps provide a highly stable load for probiotics.
[0022] 4. The antibacterial composite hydrogel in this invention uses sodium alginate / calcium chloride to encapsulate probiotics to obtain core-shell microspheres, which resist processing and water impact. The gelatin-tannic acid hydrogel network slowly releases bacteria to maintain the activity of functional bacteria. Multiple probiotics degrade pollutants and inhibit pathogens, while tannic acid chemically destroys the membrane structure of pathogenic microorganisms, simultaneously addressing the needs of organic matter decomposition, ammonia nitrogen conversion, and disease control. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments in the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1: An aquaculture water quality improver, comprising the following raw materials by weight: 40 parts composite biochar, 8 parts bentonite, 50 parts deionized water, 8 parts hollow glass microspheres, 16 parts cod liver oil and 35 parts antibacterial composite hydrogel.
[0025] The preparation method of this aquaculture water quality improver includes the following steps: Step 1: Add composite biochar, bentonite, and deionized water to a ball mill and mill for 20 minutes. Then add hollow glass microspheres and mill for 10 minutes to obtain the main material. Add cod liver oil and antibacterial composite hydrogel to an emulsifier and homogenize and emulsify for 10 minutes to obtain the auxiliary material. Step 2: Close the glue outlets on both sides of the fully automatic pellet press, preheat the glue outlets to 30°C, connect the glue pipe and air pipe, and transport the main material into the gelatin box. Open the glue outlet to form a continuous gelatin strip. When the strip passes through the rotating mold, add the auxiliary material. The mold presses the strip to form an elliptical pellet. Dry at 30°C for 2 hours, spray with 10wt% citric acid ethanol solution for 10 seconds, and vacuum dry to obtain an aquaculture water quality improver.
[0026] Through gradient density encapsulation, hollow glass microspheres adjust the density to suspend the water quality improver in the water, low-temperature pelletizing protects the bacterial community, and citric acid cross-linked gelatin achieves rapid adsorption and degradation of ammonia nitrogen and heavy metals by the outer layer of composite biocarbon, buffering salinity changes by the middle layer of bentonite, and slow-release of bacterial community by the core hydrogel, thus extending the effect of use; achieving high purification and long-lasting antibacterial effect.
[0027] Specifically, composite biochar is prepared by the following steps: Walnut shell derivatives were refluxed in 6wt% hydrochloric acid for 1 h, washed with ultrapure water until neutral, filtered, dried, and calcined at 400℃ under nitrogen protection for 2 h to obtain pretreated biochar. 9 g of titanium dioxide / iron-manganese nanosheets, 1 g of pretreated biochar, and 240 mL of deionized water were added to a reaction vessel and stirred at 300 rpm for 2 h. The mixture was then transferred to a 500 mL stainless steel reaction vessel lined with polytetrafluoroethylene and reacted at 160℃ for 6 h. After cooling to room temperature, the mixture was filtered, vacuum dried at 70℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain composite biochar.
[0028] Composite biochar was prepared by removing impurities from biochar through acid washing, retaining functional groups through nitrogen calcination, and constructing a Ti-OC chemical interface through hydrothermal bonding. This process increased the specific surface area, formed high-speed electron channels through Ti-OC bonds, and protected the active components of iron / manganese through mesopores, thereby further improving the photocatalytic degradation rate of ammonia nitrogen and the adsorption capacity of heavy metals.
[0029] Specifically, titanium dioxide / iron-manganese nanosheets are prepared by the following steps: 4.5 g of ferric chloride hexahydrate, 4.5 g of manganese sulfate, and 90 mL of deionized water were added to a reaction vessel and stirred at 60 °C for 10 min to obtain a mixed metal solution. 9.0 g of anatase nano-titanium dioxide and 0.9 L of deionized water were added to the reaction vessel and sonicated for 20 min. Then, 45 mL of the mixed metal solution, 90 mL of 1 wt% sodium citrate solution, and 450 mL of 1 wt% ascorbic acid solution were added. Nitrogen gas was introduced for 20 min, and the mixture was stirred at 300 rpm in the dark for 20 min. A 365 nm ultraviolet lamp was placed 5 cm below the liquid surface and the lamp was turned on. The mixture was reacted in a 40 °C water bath for 3 h. The suspension turned brownish-black. The solution was filtered and washed repeatedly with 1 wt% sodium citrate solution and nitrogen-saturated ethanol until the water was clear. The solution was then vacuum dried to constant weight to obtain titanium dioxide / iron-manganese nanosheets.
[0030] Ultraviolet light irradiation is used for photocatalytic reduction deposition. Under nitrogen protection, ultraviolet light excites anatase titanium dioxide to generate electron-hole pairs. With the directional regulation of sodium citrate and the synergistic reduction effect of ascorbic acid, iron and manganese ions are co-deposited on the surface of titanium dioxide to form titanium dioxide / iron-manganese nanosheets. This improves the visible light absorption rate and the adsorption effect of heavy metals, and prolongs the degradation of ammonia nitrogen.
[0031] Specifically, the antibacterial composite hydrogel is prepared by the following steps: Add 20 mL of the composite bacterial solution to the reaction vessel, centrifuge for 10 min, collect the bacterial cells, transfer to 5 mL of phosphate buffer and 10 mL of 4 wt% sodium alginate solution, stir for 20 min, then add 0.8 mL of 0.1 wt% calcium chloride solution dropwise, solidify for 20 min, and obtain core-shell antibacterial microspheres; add 3.0 g of gelatin and 30 mL of deionized water to the reaction vessel, stir at 50 °C for 20 min, add 0.5 g of tannic acid, adjust the pH to 8 with sodium hydroxide, stir for 10 min, then add 0.5 g of core-shell antibacterial microspheres, stir for 5 min, pour into a mold and freeze at -30 °C for 1 h, thaw at room temperature, and obtain antibacterial composite hydrogel.
[0032] By preparing core-shell antibacterial microspheres and double encapsulation, calcium alginate encapsulates bacteria, tannic acid, and gelatin to form an internal protective effect against bacteria and an external bactericidal effect, physically isolating probiotics from antibacterial agents. By replacing nano-metals with fully bio-based materials, the problems of heavy metal toxicity and microbial resistance in the comparative patent are solved, achieving long-term ecological and safe water quality improvement.
[0033] Specifically, the compound bacterial solution is prepared by the following steps: Add 3g of 1.5wt% shrimp shell hydrolysate, 0.6g of 0.3wt% fish meal peptone, 0.08g of 0.04wt% sodium nitrate, and 0.2g of 0.1wt% riboflavin solution to a reaction vessel, and adjust the pH to 6 with deionized water to obtain a compound bacterial culture medium. Inoculate 200g of the compound bacterial culture medium with 1.8mL of Bacillus licheniformis suspension, 1.8mL of Bacillus subtilis suspension, 2.4mL of Rhodopseudomonas palustris suspension, 3.0mL of Rhodopseudomonas sphaeroides suspension, and 1.0mL of Bacillus lysinogen suspension, and incubate at 30℃ for 100h to obtain a compound bacterial solution.
[0034] By combining chitin-derived nutrients supplied by shrimp shell hydrolysate, slow-release nitrogen source provided by fish meal peptone, electron transfer optimized by sodium nitrate, and photosynthetic efficiency enhanced by riboflavin, this formula, along with the synergistic effect of five bacteria, achieves highly efficient pollutant removal and solves the problem of synergistic pollution from ammonia nitrogen, nitrite, hydrogen sulfide, and algae in aquaculture.
[0035] The hollow glass microspheres have a density of 0.1–0.6 g / cm³ and a particle size of 10–200 μm; the gelatin tape has a thickness of 0.3 mm; and the elliptical capsules have a size of 5 × 7 mm.
[0036] The application method of aquaculture water quality improver includes the following steps: For open ponds, use water quality improver at 200g / mu·m; for recirculating water systems, add 50g / m³. 3 For cage culture, use 100g / bag (net bag: 40×60cm) per 10m² 3 Hang one bag; before use, mix 1g of improver with 10mL of water and stir for 10-20 minutes to activate it. After activation, in open ponds, evenly sprinkle it against the wind and inject it into the circulating water system according to the ratio. The net cages are suspended at a water depth of 1.5-3m. Oxygenation should be carried out simultaneously throughout the addition process to promote the release of active substances through water flow.
[0037] Example 2: An aquaculture water quality improver, comprising the following raw materials by weight: 45 parts of composite biochar, 9 parts of bentonite, 55 parts of deionized water, 9 parts of hollow glass microspheres, 18 parts of cod liver oil and 37.5 parts of antibacterial composite hydrogel.
[0038] The preparation method of this aquaculture water quality improver includes the following steps: Step 1: Add composite biochar, bentonite, and deionized water to a ball mill and mill for 25 minutes. Then add hollow glass microspheres and mill for 15 minutes to obtain the main material. Add cod liver oil and antibacterial composite hydrogel to an emulsifier and homogenize and emulsify for 12.5 minutes to obtain the auxiliary material. Step 2: Close the gelatin outlets on both sides of the fully automatic pellet press, preheat the gelatin outlets to 35°C, connect the gel pipe and air pipe, and transport the main material into the gelatin box. Open the gelatin outlet to form a continuous gelatin strip. When the strip passes through the rotating mold, add the auxiliary material. The mold presses the strip to form an elliptical pellet. Dry at 35°C for 2.5 hours, spray with 10wt% citric acid ethanol solution for 12.5 seconds, and vacuum dry to obtain an aquaculture water quality improver.
[0039] Specifically, composite biochar is prepared by the following steps: Walnut shell derivatives were refluxed in 6wt% hydrochloric acid for 1.5 h, washed with ultrapure water until neutral, filtered, dried, and calcined at 450℃ under nitrogen protection for 2.5 h to obtain pretreated biochar. 12 g of titanium dioxide / iron-manganese nanosheets, 2 g of pretreated biochar and 270 mL of deionized water were added to a reaction vessel and stirred at 350 rpm for 2.5 h. The mixture was then transferred to a 500 mL stainless steel reaction vessel lined with polytetrafluoroethylene and reacted at 170℃ for 7 h. After cooling to room temperature, the mixture was filtered, dried under vacuum at 75℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain composite biochar.
[0040] Specifically, titanium dioxide / iron-manganese nanosheets are prepared by the following steps: 5g of ferric chloride hexahydrate, 5g of manganese sulfate, and 95mL of deionized water were added to a reaction vessel and stirred at 65℃ for 12.5min to obtain a mixed metal solution. 10.0g of anatase nano-titanium dioxide and 0.95L of deionized water were added to the reaction vessel and sonicated for 25min. Then, 50mL of the mixed metal solution, 95mL of 1wt% sodium citrate solution, and 500mL of 1wt% ascorbic acid solution were added. Nitrogen gas was introduced for 25min, and the mixture was stirred at 325rpm in the dark for 25min. A 365nm ultraviolet lamp was placed 7.5cm below the liquid surface and the lamp was turned on. The mixture was reacted in a 45℃ water bath for 3.5h. The suspension turned brownish-black. The mixture was filtered and washed repeatedly with 1wt% sodium citrate solution and nitrogen-saturated ethanol until the water was clear. The mixture was then vacuum dried to constant weight to obtain titanium dioxide / iron-manganese nanosheets.
[0041] Specifically, the antibacterial composite hydrogel is prepared by the following steps: Add 25 mL of the composite bacterial solution to the reaction vessel, centrifuge for 12.5 min, collect the bacterial cells, transfer to 7.5 mL of phosphate buffer and 12.5 mL of 4 wt% sodium alginate solution, stir for 25 min, then add 0.9 mL of 0.1 wt% calcium chloride solution dropwise, solidify for 25 min, and obtain core-shell antibacterial microspheres; add 3.25 g of gelatin and 35 mL of deionized water to the reaction vessel, stir at 55 °C for 25 min, add 0.75 g of tannic acid, adjust the pH to 8 with sodium hydroxide, stir for 12.5 min, then add 0.75 g of core-shell antibacterial microspheres, stir for 7.5 min, pour into a mold and freeze at -25 °C for 1.5 h, thaw at room temperature, and obtain antibacterial composite hydrogel.
[0042] Specifically, the compound bacterial solution is prepared by the following steps: 4g of 1.5wt% shrimp shell hydrolysate, 0.7g of 0.3wt% fish meal peptone, 0.09g of 0.04wt% sodium nitrate, and 0.3g of 0.1wt% riboflavin solution were added to a reaction vessel, and the pH was adjusted to 6 with deionized water to obtain a compound bacterial culture medium. 2.0mL of Bacillus licheniformis suspension, 2.0mL of Bacillus subtilis suspension, 2.7mL of Rhodopseudomonas palustris suspension, 3.3mL of Rhodopseudomonas spp. suspension, and 1.25mL of Bacillus lysinensis suspension were inoculated into 250g of the compound bacterial culture medium and cultured at 35℃ for 110h to obtain a compound bacterial solution.
[0043] Example 3: An aquaculture water quality improver, comprising the following raw materials by weight: 50 parts composite biochar, 10 parts bentonite, 60 parts deionized water, 10 parts hollow glass microspheres, 20 parts cod liver oil and 40 parts antibacterial composite hydrogel.
[0044] The preparation method of this aquaculture water quality improver includes the following steps: Step 1: Add composite biochar, bentonite, and deionized water to a ball mill and mill for 30 minutes. Then add hollow glass microspheres and mill for 20 minutes to obtain the main material. Add cod liver oil and antibacterial composite hydrogel to an emulsifier and homogenize and emulsify for 15 minutes to obtain the auxiliary material. Step 2: Close the glue outlets on both sides of the fully automatic pellet press, preheat the glue outlets to 40°C, connect the glue pipe and air pipe, and transport the main material into the gelatin box. Open the glue outlet to form a continuous gelatin strip. When the strip passes through the rotating mold, add the auxiliary material. The mold presses the strip to form an elliptical capsule. Dry at 40°C for 3 hours, spray with 10wt% citric acid ethanol solution for 15 seconds, and vacuum dry to obtain an aquaculture water quality improver.
[0045] Specifically, composite biochar is prepared by the following steps: Walnut shell derivatives were refluxed in 6wt% hydrochloric acid for 2 hours, washed with ultrapure water until neutral, filtered, dried, and calcined at 500℃ under nitrogen protection for 3 hours to obtain pretreated biochar. 15g of titanium dioxide / iron-manganese nanosheets, 3g of pretreated biochar, and 300mL of deionized water were added to a reaction vessel and stirred at 400rpm for 3 hours. The mixture was then transferred to a 500mL stainless steel reaction vessel lined with polytetrafluoroethylene and reacted at 180℃ for 8 hours. After cooling to room temperature, the mixture was filtered, dried under vacuum at 80℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain composite biochar.
[0046] Specifically, titanium dioxide / iron-manganese nanosheets are prepared by the following steps: 5.5 g of ferric chloride hexahydrate, 5.5 g of manganese sulfate, and 100 mL of deionized water were added to a reaction vessel and stirred at 70 °C for 15 min to obtain a mixed metal solution. 11.0 g of anatase nano-titanium dioxide and 1.0 L of deionized water were added to the reaction vessel and sonicated for 30 min. Then, 55 mL of the mixed metal solution, 100 mL of 1 wt% sodium citrate solution, and 550 mL of 1 wt% ascorbic acid solution were added. Nitrogen gas was introduced for 30 min, and the mixture was stirred at 350 rpm in the dark for 30 min. A 365 nm ultraviolet lamp was placed 10 cm below the liquid surface and the lamp was turned on. The mixture was reacted in a 50 °C water bath for 4 h. The suspension turned brownish-black. The solution was filtered and washed repeatedly with 1 wt% sodium citrate solution and nitrogen-saturated ethanol until the water was clear. The solution was then vacuum dried to constant weight to obtain titanium dioxide / iron-manganese nanosheets.
[0047] Specifically, the antibacterial composite hydrogel is prepared by the following steps: Add 30 mL of the composite bacterial solution to the reaction vessel, centrifuge for 15 min, collect the bacterial cells, transfer to 10 mL of phosphate buffer and 15 mL of 4 wt% sodium alginate solution, stir for 30 min, then add 1.0 mL of 0.1 wt% calcium chloride solution dropwise, solidify for 30 min, and obtain core-shell antibacterial microspheres; add 3.5 g of gelatin and 40 mL of deionized water to the reaction vessel, stir at 60 °C for 30 min, add 1.0 g of tannic acid, adjust the pH to 8 with sodium hydroxide, stir for 15 min, then add 1.0 g of core-shell antibacterial microspheres, stir for 10 min, pour into a mold and freeze at -20 °C for 2 h, thaw at room temperature, and obtain antibacterial composite hydrogel.
[0048] Specifically, the compound bacterial solution is prepared by the following steps: Add 5g of 1.5wt% shrimp shell hydrolysate, 0.8g of 0.3wt% fish meal peptone, 0.10g of 0.04wt% sodium nitrate, and 0.4g of 0.1wt% riboflavin solution to a reaction vessel, and adjust the pH to 6 with deionized water to obtain a compound bacterial culture medium. Inoculate 300g of the compound bacterial culture medium with 2.2mL of Bacillus licheniformis suspension, 2.2mL of Bacillus subtilis suspension, 3.0mL of Rhodopseudomonas palustris suspension, 3.6mL of Rhodopseudomonas spp. suspension, and 1.5mL of Bacillus lysinensis suspension, and incubate at 40℃ for 120h to obtain a compound bacterial solution.
[0049] The raw materials used in Examples 1-3 of this application are all commercially available. For example, hollow glass microspheres were selected from Hebei Huishun Mining Co., Ltd. (Huishun Mining); walnut shell derivatives were selected from Lingshou County Yaoyang Mineral Products Processing Plant (Yaoyang); anatase nano-titanium dioxide was selected from Nanjing Tianxing New Materials Co., Ltd. (TTP-A12); Bacillus licheniformis suspension was selected from Pusrui (Shanghai) Biomedical Co., Ltd. (SHMCC); Bacillus subtilis suspension was selected from Hangzhou Muyun Technology Co., Ltd. (ACEtest); Rhodopseudomonas palustris suspension was selected from Shanghai Lianmai Bioengineering Co., Ltd. (ATCC336448); Rhodopseudomonas sphaeroides suspension was selected from Beijing Bio-Biobio Biotechnology Co., Ltd. (bio-56574); and enzyme-producing lysinus suspension was selected from Shanghai Xuanke Biotechnology Co., Ltd. (XK-JZ-1020).
[0050] Comparative Example 1: The difference from Example 3 is that anatase nano-titanium dioxide and ultraviolet irradiation are not added in the step of preparing titanium dioxide / iron-manganese nanosheets, while the other steps remain unchanged to prepare a water quality improver.
[0051] Comparative Example 2: The difference from Example 3 is that, in the step of preparing composite biochar, corn stalk derivatives are used instead of walnut shell derivatives, while the other steps remain unchanged, to prepare a water quality improver.
[0052] Comparative Example 3: The difference from Example 3 is that the antibacterial composite hydrogel is prepared without the coating of sodium alginate and calcium chloride, while the other steps remain unchanged to prepare the water quality improver.
[0053] The water quality improvers prepared in Examples 1-3 and Comparative Examples 1-3 were applied to open-air ponds with poor water color and deteriorated water quality at a ratio of 200 g / mu·m. After 7 days, the adsorption rate, impurity removal rate, chemical oxygen demand (COD), and COD degradation rate were tested, and the results are shown in Table 1. Table 1: Performance Test Results of Aquaculture Water Quality Improvers Adsorption rate % 95.5 96.2 97.5 67.1 63.8 78.6 Impurity removal rate % 92.2 92.7 93.3 78.9 74.4 68.7 Chemical oxygen demand (mg / L) 13.3 12.4 11.8 48.1 37.6 30.2 Chemical oxygen demand degradation rate (%) 95.3 95.7 96.6 70.1 81.1 75.6 As can be seen from Table 1, the water quality improvers prepared in Examples 1-3 have significantly better purification effects than those in Comparative Examples 1-3. They utilize the high specific surface area of walnut shell biochar and the efficient adsorption of pollutants by bentonite, while titanium dioxide / iron-manganese nanosheets rapidly degrade ammonia nitrogen under ultraviolet light and adsorb heavy metals. The probiotics encapsulated in calcium alginate provide slow-release antibacterial effects and stabilize the microecology. They synergistically achieve a three-in-one effect of "adsorption-photocatalytic degradation-biological antibacterial", significantly improving the removal rate of organic matter and the stability of water quality.
[0054] In Comparative Example 1, the significant decrease in the degradation rate of chemical oxygen demand (COD) and the significant increase in COD may be due to the lack of anatase nano-titanium dioxide and ultraviolet lamp irradiation. This greatly reduces the photocatalytic effect of titanium dioxide / iron-manganese nanosheets in producing highly oxidizing active substances under ultraviolet excitation, resulting in adsorbed biochar being able to only enrich pollutants and not completely decompose them. This directly weakens the chemical degradation capacity of organic matter and causes the continuous accumulation of organic matter.
[0055] In Comparative Example 2, the adsorption rate decreased significantly, which may be due to the structural performance degradation caused by replacing walnut shell derivatives with corn stalk derivatives. The dense woody structure of walnut shells can form hierarchical pores, and its micropores and mesopores can synergistically adsorb pollutants of different molecular weights. In addition, the carbon surface of walnut shells has high roughness, and titanium dioxide / iron-manganese nanosheets are firmly bonded. The corn stalks have high ash content, and the ash melts and blocks the pores during high-temperature calcination. In addition, the high hemicellulose content produces more alkaline ash during pyrolysis, which reduces the specific adsorption of heavy metals / organic acids.
[0056] In Comparative Example 3, the impurity removal rate decreased significantly. This may be because without coating with sodium alginate and calcium chloride, the uncoated bacteria became inactive due to exposure to salinity, pH fluctuations, and competition from native microorganisms in the aquatic environment. At the same time, due to uncontrolled density, they could not target the pollution-rich area and lost their core ability to decompose and inhibit pathogenic microorganisms, thus reducing the efficiency of biological impurity removal.
[0057] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A water quality improver for aquaculture, characterized in that, By weight, the raw materials include the following components: 40-50 parts composite biochar, 8-10 parts bentonite, 50-60 parts deionized water, 8-10 parts hollow glass microspheres, 16-20 parts cod liver oil and 35-40 parts antibacterial composite hydrogel; The composite biochar is prepared by combining walnut shell derivatives and titanium dioxide / iron-manganese nanosheets. The titanium dioxide / iron-manganese nanosheets were prepared by the following steps: Ferric chloride hexahydrate, manganese sulfate, and deionized water were stirred to obtain a mixed metal solution. Anatase nano-titanium dioxide, deionized water, the mixed metal solution, 1 wt% sodium citrate solution, and 1 wt% ascorbic acid solution were stirred under nitrogen atmosphere in the dark and then photocatalytically reduced to obtain titanium dioxide / iron-manganese nanosheets. The composite biochar is prepared by the following steps: Walnut shell derivatives were acid-washed and refluxed for 1-2 hours, washed with ultrapure water until neutral, filtered, dried, and calcined at 400-500℃ under nitrogen protection for 2-3 hours to obtain pretreated biochar. Titanium dioxide / iron-manganese nanosheets, pretreated biochar, and deionized water were added to a reaction vessel and stirred at 300-400 rpm for 2-3 hours. The mixture was then transferred to a 500 mL stainless steel reaction vessel lined with polytetrafluoroethylene and reacted at 160-180℃ for 6-8 hours. After cooling to room temperature, the mixture was filtered, vacuum dried at 70-80℃ to constant weight, ground, and passed through a 100-mesh sieve to obtain composite biochar. The ratio of titanium dioxide / iron-manganese nanosheets, pretreated biochar, and deionized water is 9-15g: 1-3g: 240-300mL. The titanium dioxide / iron-manganese nanosheets are prepared by the following steps: Ferric chloride hexahydrate, manganese sulfate, and deionized water were added to a reaction vessel and stirred at 60-70℃ for 10-15 min to obtain a mixed metal solution. Anatase nano-titanium dioxide and deionized water were added to the reaction vessel and sonicated for 20-30 min. Then, the mixed metal solution, 1 wt% sodium citrate solution, and 1 wt% ascorbic acid solution were added. Nitrogen gas was introduced for 20-30 min, and the mixture was stirred in the dark at 300-350 rpm for 20-30 min. A 365 nm ultraviolet lamp was placed 5-10 cm below the liquid surface and the lamp was turned on. The mixture was reacted in a water bath at 40-50℃ for 3-4 h. The suspension turned brownish-black. The mixture was filtered and washed repeatedly with 1 wt% sodium citrate solution and nitrogen-saturated ethanol until the water was clear. The mixture was then vacuum dried to constant weight to obtain titanium dioxide / iron-manganese nanosheets. The antibacterial composite hydrogel is prepared by the following steps: Add the composite bacterial solution to the reaction vessel, centrifuge for 10-15 min, collect the bacterial cells, transfer to phosphate buffer and 4 wt% sodium alginate solution and stir for 20-30 min, then add 0.1 wt% calcium chloride solution dropwise and solidify for 20-30 min to obtain core-shell antibacterial microspheres; add gelatin and deionized water to the reaction vessel, stir at 50-60℃ for 20-30 min, add tannic acid, adjust the pH to 8 with sodium hydroxide, stir for 10-15 min, then add the core-shell antibacterial microspheres, stir for 5-10 min, pour into a mold and freeze at -30℃ to -20℃ for 1-2 h, thaw at room temperature to obtain antibacterial composite hydrogel; The compound bacterial solution is prepared by the following steps: Add 1.5wt% shrimp shell hydrolysate, 0.3wt% fish meal peptone, 0.04wt% sodium nitrate and 0.1wt% riboflavin solution to a reaction vessel, adjust the pH to 6 with deionized water to obtain a compound bacterial culture medium; inoculate Bacillus licheniformis suspension, Bacillus subtilis suspension, Rhodopseudomonas palustris suspension, Rhodopseudomonas sphaeroides suspension and Bacillus lysinogen suspension into the compound bacterial culture medium, and culture at 30-40℃ for 100-120 h to obtain a compound bacterial solution; The preparation method of the aquaculture water quality improver includes the following steps: Step 1: Add composite biochar, bentonite, and deionized water to a ball mill and mill for 20-30 minutes. Then add hollow glass microspheres and mill for 10-20 minutes to obtain the main material. Add cod liver oil and antibacterial composite hydrogel to an emulsifier and homogenize and emulsify for 10-15 minutes to obtain the auxiliary material. Step 2: Close the glue outlets on both sides of the fully automatic pellet press, preheat the glue outlets to 30-40℃, connect the glue tube and air tube, and transport the main material into the gelatin box. Open the glue outlet to form a continuous gelatin strip. When the strip passes through the rotating mold, add the auxiliary material. The mold presses the strip to form an elliptical pellet. Dry it at 30-40℃ for 2-3 hours, spray it with a 10wt% citric acid ethanol solution for 10-15 seconds, and vacuum dry it to obtain an aquaculture water quality improver.
2. The aquaculture water quality improver according to claim 1, characterized in that, The ratio of the amount of ferric chloride hexahydrate, manganese sulfate, and deionized water is 4.5-5.5g: 4.5-5.5g: 90-100mL; the ratio of the amount of anatase nano-titanium dioxide, deionized water, mixed metal solution, sodium citrate solution, and ascorbic acid solution is 9.0-11.0g: 0.9-1.0L: 45-55mL: 90-100mL: 450-550mL.
3. The aquaculture water quality improver according to claim 1, characterized in that, The ratio of the amount of the compound bacterial solution, phosphate buffer, sodium alginate solution and calcium chloride solution is 20-30 mL: 5-10 mL: 10-15 mL: 0.8-1.0 mL; the ratio of the amount of the gelatin, deionized water, tannic acid and core-shell antibacterial microspheres is 3.0-3.5 g: 30-40 mL: 0.5-1.0 g: 0.5-1.0 g.
4. The aquaculture water quality improver according to claim 1, characterized in that, The mass ratio of the shrimp shell hydrolysate, fish meal peptone, sodium nitrate, and riboflavin is 3-5:0.6-0.8:0.08-0.1:0.2-0.4; the volume ratio of the Bacillus licheniformis suspension, Bacillus subtilis suspension, Rhodopseudomonas palustris suspension, Rhodopseudomonas sphaeroides suspension, Bacillus thuringiensis suspension, and the compound culture medium is 1.8-2.2 mL:1.8-2.2 mL:2.4-3.0 mL:3.0-3.6 mL:1.0-1.5 mL:200-300 g.
Citation Information
Patent Citations
Water quality improver for aquatic products and preparation method thereof
CN117446886A
Carbon-coated nanosphere for water quality purification and preparation method of carbon-coated nanosphere
CN112973646A
Aquaculture water purifying agent based on compound microorganisms and preparation method of aquaculture water purifying agent
CN119161031A